System geometric interpretation - Mykytas, M. (Ways to Improve Construction Efficiency, 2019)
The article describes one of the stages of developing effective methods for analyzing the set of possible development scenarios and forecasting the effectiveness of the functioning of clusters. The purpose of this article is to search for approaches and concepts to objectivize and identify the main structural system elements of an energy-efficient architectural and construction cluster with adaptive properties. A “cluster” model can be viewed as a collapsible-structured model with geometric components, a geometric design or a geometric representation of an element model can describe the representations of a set of geometric and graphical methods. The main ways to objectify the system of key indicators are defined. Due to the fact that the internal structure of an adaptive energy-efficient architectural and construction cluster contains a significant number of structural elements, their analysis and coordination require separate consideration in subsequent publications.